PENGARUH SISTEM PERPAJAKAN, SANKSI PERPAJAKAN DAN TARIF PAJAK TERHADAP PERSEPSI WAJIB PAJAK MENGENAI ETIKA PENGGELAPAN PAJAK - Icha Felicia; Teguh Erawati (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
This study examines to the influence of tax system, tax sanction, and tax rates on perception taxpayer about ethich tax evasion. The population in the special region of Yogyakarta. The sample in this study is determined by sampling convinience method, the data collected with the distribution of questionnaires. The method of analysis used is multiple linear regression. Based on the results of the analysis indicate that the tax system negatif and not significant on perception taxpayer about ethich tax evasion , tax sanction has positivie and significant on perception taxpayer about ethich tax evasion, and tax rates positive and significant on perception taxpayer about ethich tax evasion. The most dominant variable influencing on perception taxpayer ethich tax evasion perceptions about the ethical of tax sanction because it has a beta value of 0.354 standard coefficient.